The genus Phyllomyza Fallén from China, with descriptions of three new species (Diptera, Milichiidae) - Yu-Qiang Xi; Ding Yang; Xin-Ming Yin (ZooKeys, 2018)
The following three species of the genus Phyllomyza Fallén from China are described as new to science: P. guangxiensis sp. n., P. luteigenis sp. n., and P. quadratpalpus sp. n. A key to the known species of Phyllomyza from China is presented.